Effect of Contact Time on Interface Reaction between Aluminum Silicon (7% and 11%) Alloy and Steel Dies SKD 61 - Suharno, Bambang; Nurhayati, Neni Octapiani; Arifin, Bustanul; Harjanto, Sri (UI Scholars Hub, 2007)
Effect of Contact Time on Interface Reaction between Aluminum Silicon (7% and 11%) Alloy and Steel Dies SKD 61. Die soldering (die sticking) is a defect of metal casting in which molten metal “welds” to the metallic die mold surface during casting process. Die soldering is the result of an interface reaction between the molten aluminum and the die material. Aluminum alloy with 7 and 11% silicon and SKD 61 die steel are the most common melt and die material used in aluminum die casting. This research is done to study the morphology and the characteristics of the formed AlxFeySiz intermetallic layer during interface reaction at dipping test. The samples of as-anneal SKD 61 tool steel was dipped into the molten of Al-7%Si held at temperature 680oC and into molten Al-11%Si held at temperature 710oC with the different contact time of 10 minutes; 30 minutes; and 50 minutes. The research results showed that the interface reaction can form a compact intermetallic layer with AlxFey phase and a broken intermetallic layer with AlxFeySiz phase on the surface of SKD 61 tool steel. The increasing of the contact time by the immersion of material SKD 61 tool steel in both of molten Al-7%Si and Al-11%Si will increase the thickness of the AlxFeySiz intermetallic layer until an optimum point and then decreasing. The micro hardness of the AlxFeySiz intermetallic layer depends on the content of the iron. Increasing of the iron content in intermetallic layer will increase the micro hardness of the AlxFeySiz. This condition happened because the increasing of Fe content will cause forming of intermetallic AlxFeySiz phase becomes quicker.